2022
DOI: 10.3390/separations9020023
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Design Approach for Quantitative Expressions of Simultaneous Quantification of Two Binary Formulations Containing Remogliflozin and Gliptins by RP-HPLC

Abstract: The aim of this study was to develop a fast RP-HPLC method for simultaneous measurement of two antidiabetic formulations (vildagliptin + remogliflozin and teneligliptin + remogliflozin) under identical experimental conditions. Using the Box–Behnken approach and response surface design, the interaction and quadratic influence of three variable parameters, acetonitrile %, pH of the mobile phase, and flow rate, on resolution between the peaks were optimized. To forecast the resolution of peaks (2.7 and 6.5) for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The break at pH = 9.0 is related to the pK a value of VILD; this is due to changes in the protonation-deprotonation equilibrium of the VILD drug. This pK a1 value is very close to the value of VILD in the literature that equal to 9.03 [21,63,64].…”
Section: Study Of the Ph Effectsupporting
confidence: 87%
“…The break at pH = 9.0 is related to the pK a value of VILD; this is due to changes in the protonation-deprotonation equilibrium of the VILD drug. This pK a1 value is very close to the value of VILD in the literature that equal to 9.03 [21,63,64].…”
Section: Study Of the Ph Effectsupporting
confidence: 87%
“…A preliminary study showed that using more than 70% acetonitrile in the mobile phase eluted MF after 7 min at a pH less than 5.5, whereas baseline separation between VD and MF was not achieved. Separation quality is important; thus, the typical key response is good resolution between critical analyte peaks [ 56 , 57 , 58 ]. Similar work has been reported on different drugs in which the resolution was the only response, while buffer pH, percentage acetonitrile, and flow rate had a significant effect on the response [ 51 , 52 , 53 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Separation quality is important; thus, the typical key response is good resolution between critical analyte peaks [ 56 , 57 , 58 ]. Similar work has been reported on different drugs in which the resolution was the only response, while buffer pH, percentage acetonitrile, and flow rate had a significant effect on the response [ 51 , 52 , 53 , 58 ]. The three-level face-centered central composite design suggested by the software and the resolution results are tabulated below ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Attimarad et al developed simultaneous quantification of two binary formulations containing remogliflozin and gliptins. 2 Dhara et al developed a UV spectroscopic method for determination of remogliflozin etabonate in bulk and tablet dosage form. 3 Attimarad et al developed multicomponent antidiabetic formulation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…There was only one article available for the content determination using the UV spectroscopy, but this method is not suitable for shelf life analysis due to the lack of stability indicating nature. Attimarad et al developed simultaneous quantification of two binary formulations containing remogliflozin and gliptins . Dhara et al developed a UV spectroscopic method for determination of remogliflozin etabonate in bulk and tablet dosage form .…”
Section: Introductionmentioning
confidence: 99%